The comparative effect of paired versus a small group cross motor invention on the motor capabilities of selected children pre-identified with childhood apraxia of speech - Nolte, Heike (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018